1951
DOI: 10.1002/hlca.19510340406
|View full text |Cite
|
Sign up to set email alerts
|

Reduktionen einiger Toluolsulfonsäureester von Steroiden mittels Lithiumaluminiumhydrid

Abstract: Nachdem gezeigt worden war1), dass Cholesterin-toluol-sulfonsaureester durch Lithiumaluminiumhydrid zu iso-Cholesten und Cholesten reduziert wird, haben wir Tosylester anderer Steroide dem gleichen Reduktionsverfahren unterworfen. Es interessierten uns dabei zwei Fragen: 1. ob auch bei Steroidtosylestern die zweite Art der reduktiven Spaltung von Tosylestern, die xu den entsprechenden freien Hydroxylderivaten fuhrtl), vorkommt, und 2. ob sich weitere Beispiele von Steroid-tosylestern finden lassen, die durch L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0
2

Year Published

1952
1952
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
0
6
0
2
Order By: Relevance
“…Methyl 4-0-Benzoyl-6-bromo-2,3,6-trideoxy-a-D-ery+ro-hexopyranoside (3).-To a solution of methyl 4,6-0-benzylidene-2,3dideoxy-t*-D-en/</iro-hexopyranoside (2, 4.00 g, 16 mmol) in dry carbon tetrachloride (100 ml) was added V-bromosuccinimide (3.14 g, 17.6 mmol) and barium carbonate (4 g). The mixture was refluxed for 1.5 hr and then cooled to 0°.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methyl 4-0-Benzoyl-6-bromo-2,3,6-trideoxy-a-D-ery+ro-hexopyranoside (3).-To a solution of methyl 4,6-0-benzylidene-2,3dideoxy-t*-D-en/</iro-hexopyranoside (2, 4.00 g, 16 mmol) in dry carbon tetrachloride (100 ml) was added V-bromosuccinimide (3.14 g, 17.6 mmol) and barium carbonate (4 g). The mixture was refluxed for 1.5 hr and then cooled to 0°.…”
Section: Methodsmentioning
confidence: 99%
“…Hydrogenation could be terminated readily at the point of saturation of the double bond, with no detectable hydrogenolysis of the O-benzylidene group. Treatment of the saturated acetal 2 with iV-bromosuccinimide in refluxing carbon tetrachloride12,13 gave methyl 4-O-benzoyl-6-bromo-2,3,6-trideoxy-a-D-en/</tro-hexopyranoside (3) in 86% yield as an analytically pure syrup. The ir and nmr spectra of 3 confirmed that a benzoate group was present, and the fact that the conversion of 2 into the bromo benzoate had involved a substantial downfield shift of the H-4 signal confirmed that the benzoyloxy group was indeed attached at C-4; the structure 3 was also established independently as the result of further transformations.…”
mentioning
confidence: 99%
“…69,521 (1991 (10) rneilleur des cas, sur le rntlange brut des deux cttones obtenues par oxydation des alcools issus de la voie A au rnoyen du rtactif de Jones. Cette cttone 8 s'est avtrte tres instable; les tentatives de purification (distillation ou passage sur colonne de silice) n'ont fait que dirninuer sa teneur dans les rntlanges 8 + 9.Divers melanges de ces deux cttones, places dans des conditions tpirntrisantes, en prtsence de tritthylarnine (12), ont conduit 2 un rntlange 8 + 9 de composition a 1'Cquilibre 5 : 95.Les perhydrocyclododtca[b]furanes 1 0 et 11, cornposts connus (4-6), ont t t t obtenus i partir soit du rntlange d'alcools saturts 4-6 par rtduction de leurs tosylates au rnoyen de LiAIH, (13,14), soit du melange a l'tquilibre des cttones saturtes 8 + 9 par reduction de Wolff-Kishner dans la modification de Huang-Minlon (15). La sttrtochirnie de chacune de ces rtductions, bien qu'elle soit irnprtvisible dans le cas d'une reduction de Wolff-Kishner (16), n'a pas fait l'objet d'ttudes de notre part.…”
unclassified
“…Les perhydrocyclododtca[b]furanes 1 0 et 11, cornposts connus (4-6), ont t t t obtenus i partir soit du rntlange d'alcools saturts 4-6 par rtduction de leurs tosylates au rnoyen de LiAIH, (13,14), soit du melange a l'tquilibre des cttones saturtes 8 + 9 par reduction de Wolff-Kishner dans la modification de Huang-Minlon (15). La sttrtochirnie de chacune de ces rtductions, bien qu'elle soit irnprtvisible dans le cas d'une reduction de Wolff-Kishner (16), n'a pas fait l'objet d'ttudes de notre part.…”
unclassified
“…A^Cholesten-ia-ol (XX). This compound was prepared according to the method of Karrer, et al (10). The material so obtained melted at 143-144°, [a]?…”
mentioning
confidence: 99%